Seroprevalence for Human Cytomegalovirus in samples from dialysis and kidney transplanted patients - Patricia Okubo; Waldir Verissimo da Silva Junior; Edna Maria Vissoci Reiche; Miria Ramos; Sueli Donizete Borelli; João Bedendo (Rev Rene)
he aim of this study was at investigating the seroprevalence of Human Cytomegalovirus in dialysis and kidney transplanted patients and the association with hemodialysis and sex. It is a cross sectional study made in 2011 and 2012 in the county of Maringá, PA, Brazil. The studied population consisted of 203 dialysis patients and 53 kidney transplanted patients and the viral identification was made through serological technique. The study found 96% (195) seropositivity for anti-HCMV IgG in dialysis patients and 100% in the transplanted ones; 5% (10) seropositivity for anti-HCMV-IgM in dialysis patients and 37.7% (20) in transplanted ones. Performing Fisher’s exact test, there was no significant association between the seroprevalence of anti-HCMV with hemodialysis and gender. A large number of infected patients suggest the importance of nursing care to avoid cross-infection during routine procedures.